Review of Myofibroblastoma of Breast and Its Most Common Mimickers - Huang, MD, PhD, Ying; Chen, MD, PhD, Frank (North American Journal of Medicine and Science, 2012)
Myofibroblastoma (MFB) is characterized as a benign stromal neoplasm composed of uniform, bland-looking spindle cells that are often arranged in fascicles separated by thick band of collagenous stroma. Variable cellularity is common. Immunohistochemically, the spindle cells are positive for CD34, vimentin, BCL-2, ER, PR, focally positive for smooth muscle actin and negative for cytokeratin, S-100 and CD117. Although classic MFB is typically a bland-looking spindle cell tumor, some unusual morphologic variants may show worrisome malignant-looking cells. Recognition of MFB variants and its wide variety of mimickers is very important for pathologists to arrive at the correct diagnosis, and avoid misdiagnosis of malignancy.